2007
DOI: 10.1021/jp075638c
|View full text |Cite
|
Sign up to set email alerts
|

Shock Tube Study of the Reaction of CH with N2:  Overall Rate and Branching Ratio

Abstract: We have studied the reaction between CH and N2, (1) CH + N2 --> products, in shock tube experiments using CH and NCN laser absorption. CH was monitored by continuous-wave, narrow-line-width laser absorption at 431.1 nm. The overall rate coefficient of the CH + N2 reaction was measured between 1943 and 3543 K, in the 0.9-1.4 atm pressure range, using a CH perturbation approach. CH profiles recorded upon shock-heating dilute mixtures of ethane in argon and acetic anhydride in argon were perturbed by the addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
85
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(104 citation statements)
references
References 49 publications
18
85
1
Order By: Relevance
“…The fast unimolecular decomposition of NCN 3 generates NCN in its singlet excited electronic state, which undergoes a collision-induced intersystem crossing (CIISC) process to the triplet ground state ( 3 NCN stated in the following as NCN). Our previous work showed that the CIISC process is the ratelimiting process for NCN formation at temperatures above 700 K, but is still fast compared to the reaction NCN + O 2 measured here [22].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fast unimolecular decomposition of NCN 3 generates NCN in its singlet excited electronic state, which undergoes a collision-induced intersystem crossing (CIISC) process to the triplet ground state ( 3 NCN stated in the following as NCN). Our previous work showed that the CIISC process is the ratelimiting process for NCN formation at temperatures above 700 K, but is still fast compared to the reaction NCN + O 2 measured here [22].…”
Section: Methodsmentioning
confidence: 99%
“…5. The error arises from the statistical fit (±25%), the uncertainties of the absolute NCN 3 and O 2 concentrations (±5%), and of the rate constants assumed for the background mechanism. The two most important reactions for NCN consumption are NCN + NCN (8) and k 9 within error limits (k 9 ± 40%) add a ±25% uncertainty.…”
Section: Ncn + Omentioning
confidence: 99%
See 1 more Smart Citation
“…First simulations with GDF-Kin 3.0 NCN and the rate constant calculated by Moskaleva Vasudevan et al [112] performed a new shocktube study of the reaction between CH and N 2 , with ethane as a CH source at high temperatures (T > 2500 K) and acetic anhydride for lower temperatures (1900 < T < 2500 K). From absorption measurements of CH and NCN concentrations and kinetic modeling of the influence of N 2 addition on the CH profile, an expression of the rate constant was derived:: k = 6.03 · 10 12 exp(−22,100/RT ) cm 3 · mole −1 · sec −1 .…”
Section: Contribution Of the Flame Structure Analysis By Spectrosco-pmentioning
confidence: 99%
“…Recently, Hanson and coworkers [41] studied the reaction between CH and N 2 in shock tube experiments using CH and NCN laser absorption. The CH measurements established NCN and H as the primary products of the CH + N 2 reaction.…”
Section: No Formation In Combustion Systemsmentioning
confidence: 99%